Association Between Time Spent Outdoors and Risk of Multiple Sclerosis. (18th January 2022) - Sebastian, Prince; Cherbuin, Nicolas; Barcellos, Lisa F.; Roalstad, Shelly; Casper, Charles; Hart, Janace; Aaen, Gregory S.; Krupp, Lauren; Benson, Leslie; Gorman, Mark; Candee, Meghan; Chitnis, Tanuja; et al.
Abstract : Background and Objectives: This study aims to determine the contributions of sun exposure and ultraviolet radiation (UVR) exposure to risk of pediatric-onset multiple sclerosis (MS). Methods: Children with MS and controls recruited from multiple centers in the United States were matched on sex and age. Multivariable conditional logistic regression was used to investigate the association of time spent outdoors daily in summer, use of sun protection, and ambient summer UVR dose in the year before birth and the year before diagnosis with MS risk, with adjustment for sex, age, race, birth season, child's skin color, mother's education, tobacco smoke exposure, being overweight, and Epstein-Barr virus infection. Results: Three hundred thirty-two children with MS (median disease duration 7.3 months) and 534 controls were included after matching on sex and age. In a fully adjusted model, compared to spending <30 minutes outdoors daily during the most recent summer, greater time spent outdoors was associated with a marked reduction in the odds of developing MS, with evidence of dose-response (30 minutes–1 hour: adjusted odds ratio [AOR] 0.48, 95% confidence interval [CI] 0.23–0.99, p = 0.05; 1–2 hours: AOR 0.19, 95% CI 0.09–0.40, p < 0.001). Higher summer ambient UVR dose was also protective for MS (AOR 0.76 per 1 kJ/m 2, 95% CI 0.62–0.94, p = 0.01). Discussion: If this is a causal association, spending more time in the sun during summer may be strongly protective against developing pediatric MS, as well as residing in a sunnier location.